2021
DOI: 10.1001/jamanetworkopen.2021.0247
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic and Socioeconomic Disparities in Management of Incident Paroxysmal Atrial Fibrillation

Abstract: IMPORTANCE In patients with paroxysmal atrial fibrillation (AF), rhythm control with either antiarrhythmic drugs (AADs) or catheter ablation has been associated with decreased symptoms, prevention of adverse remodeling, and improved cardiovascular outcomes. Adoption of advanced cardiovascular therapeutics, however, is often slower among patients from racial/ethnic minority groups and those with lower income. OBJECTIVE To ascertain the cumulative rates of AAD and catheter ablation use for the management of paro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 38 publications
5
69
0
1
Order By: Relevance
“…Studies utilizing these registries have demonstrated that Black and Hispanic patients were less likely to receive rhythm control or catheter ablation than White patients despite the presence of symptoms. 39,41 A recent meta-analysis reported similar rates of AV node ablation but lower rates of AF ablation among Black patients compared with White patients. 18 In the Atrial Fibrillation Follow-Up Investigation of Rhythm Management (AFFIRM) randomized clinical trial, 90.1% of patients were White and only 6.6% and 3.3% patients were Black and Hispanic respectively.…”
Section: Rate Control Versus Rhythm Controlmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies utilizing these registries have demonstrated that Black and Hispanic patients were less likely to receive rhythm control or catheter ablation than White patients despite the presence of symptoms. 39,41 A recent meta-analysis reported similar rates of AV node ablation but lower rates of AF ablation among Black patients compared with White patients. 18 In the Atrial Fibrillation Follow-Up Investigation of Rhythm Management (AFFIRM) randomized clinical trial, 90.1% of patients were White and only 6.6% and 3.3% patients were Black and Hispanic respectively.…”
Section: Rate Control Versus Rhythm Controlmentioning
confidence: 99%
“…Factors such as socioeconomic status and lack of supplemental insurance coverage, as well as documented sex- and race-based differences in preferences related to medical care, might contribute to delays in diagnosing AF. 41 Lack of health literacy may limit patient engagement and impact decisions for treatment of AF. Non-White patients and those with a lower education level have been shown to be less likely to receive care from a cardiologist for AF.…”
Section: Are There Delays In Presentation and Diagnosis Of Af?mentioning
confidence: 99%
See 2 more Smart Citations
“…Сьогодні на українському фармацевтичному ринку цей антиаритмічний засіб представляють декілька виробників, що ставить перед лікарем проблему вибору оптимального препарату. І економічні аспекти фармакотерапії мають не менше значення, ніж клінічні, а для значної частини пацієнтів є ключовим фактором прихильності до лікування [20]. З урахуванням цього факту препаратом вибору серед аналогів, що містять ту саму діючу речовину, повинен бути якісний генерик, що не поступається оригінальному препарату за клінічною ефективністю і безпекою, але більш доступний.…”
Section: ключові слова: аритмія; лікування; флекаїніду ацетат; фібриляція передсердь; флекаїнідunclassified